Penggunaan Material Galian dari Desa Kandang Mbelang, Lawe Bulan Untuk Pembuatan Aspal Beton Campuran Panas - Harun Harasid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Aggregate is the main component of road pavement structure, namely 90-95% of the weight of the pavement. Such a large proportion means that the quality of the aggregate used will greatly determine the overall performance of the pavement. The availability of quality aggregate is absolutely necessary to ensure the sustainability of development in the road construction sector. One area that has aggregate potential that has not been utilized optimally is Kandang Mbelang Village, Lawe Bulan. The aim of this research is to determine the characteristics of the Marshall, UCS, ITS test values ​​and the permeability of asphalt mixtures using the excavated material of Kandang Mbelang, Lawe Bulan as aggregate. This research uses experimental methods carried out in the laboratory with variations in asphalt content of 4.5%, 5%, 5.5% and 6% for the Marshall test and obtains Optimum Asphalt Content (KAO). For ITS, UCS and permeability testing, Optimum Asphalt Content was used with three samples each. Hypothesis testing for data comparison uses the T test method. The use of Kandang Mbelang aggregate in the AC-WC spec IV mixture produces a stability value of 711.5 kg, a flow value of 3.48 mm, a porosity value of 16.077%, a density value of 2.016 gr/ cm3 and Marshall Quotient value 215.823 kg/mm ​​at Optimum Asphalt Content of 5.3%. The average ITS value is 319.024 KPa, the average UCS value is 6,982.237 KPa, while the average permeability coefficient value is 7.14x10-4 cm/s. Through the T test statistical method, it is known that the use of the Kandang Mbelang aggregate for the AC-WC spec IV mixture does not cause changes in the stability, flow, ITS and UCS values. Real changes only occur for density values, porosity values ​​and permeability coefficients.